Carbon fiber polypropylene interphase modification as a route to improved toughness. (August 2022) - Randall, James D.; Stojcevski, Filip; Djordjevic, Nemanja; Hendlmeier, Andreas; Dharmasiri, Bhagya; Stanfield, Melissa K.; Knorr, Daniel B.; Tran, Ngon T.; Varley, Russell J.; Henderson, Luke C.
Abstract: This manuscript describes the rapid surface modification of carbon fibers using small molecules for application in polypropylene composites at 10% and 40% weight fractions. Attachment of an n -butylphenyl species onto the fiber surface and incorporation into homo-polypropylene resulted in a significant toughness improvement, of 32% and 30% at 10% and 40% weight fractions respectively, when compared against untreated control samples. Further examination of the embedded fiber length, fiber weight fraction, and polymer thermal properties (e.g. Tm and Tc ) showed no differences between untreated and treated samples. However, it is proposed that the mechanical performance changes originated from the installed surface chemistry blending with the polymer phase. This is observed through experimental testing which suggests that the sliding interactions of the fiber-matrix interface has created a material that possesses superior ductility and toughness.